Representations of race relations in the classroom: the black in the everyday school life - Wilma de Nazaré Baía Coelho; Rafaela Paiva Costa (Universidade Federal de Santa Maria, 2015)
This paper presents some preliminaries results of a research that investigates the representations about race, color, Difference, Prejudgment and Racial Discrimination of the school's agents teachers, employees and students) on the quotidian of the History's, Portuguese's and Art's classes of the first two year of the secondary education of a Belém-PA's private school, in order to understand the place of the black people in the school pedagogic practices, regarding the obligation of touching racial subjects as established by the low 10.639/2003. Using the methodological and theoretic approach of Pierre Bourdieu and Roger Chartier, we analyzed the representations obtained by the non-participative observation in those classes. We realized that teachers almost didn't know anything about the low 10.639/2003 and about the ethnic and racial question on Brazil, what brings as result the reproduction of racial prejudgment and discrimination by the students. Our analysis aims, from understanding the problems with teacher development, to understand the problems related to the ethnic and racial question at school and propose solutions.